Dampak Program Pendayagunaan Zakat Produktif Terhadap Kesejahteraan Mustahik Dengan Menggunakan Pendekatan Center of Islamic Bussiness and Ecenomics Studies(CIBEST) di Kecamatan Nalumsari Jepara (Studi Kasus Baznas Kabupaten Jepara) - Suparwi S; Salsabila S; Syaifa Maulida; Fary Isvaniroh; M. Khamizul Fuadi; Nisaul Karimah (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Utilization of productive zakat is considered to be able to reduce the problem of poverty in our country. In measuring poverty, it can be measured using the Center Of Islamic Business And Economics Studies (CIBEST) approach. The CIBEST approach measures poverty based on material and spiritual aspects. The purpose of this study was to determine the impact of the productive zakat utilization program by BAZNAS Jepara Regency on mustahik in Nalumsari District. This research uses a quantitative approach with descriptive methods. The number of respondents in this study amounted to 15 mustahik household heads. The results of the study show that with the existence of a productive zakat utilization program, productive zakat utilization at BAZNAS Jepara Regency is measured based on the CIBEST approach is effective, seen based on the analysis of the CIBEST model carried out, namely quadrant I the prosperous category increased from 10 households to 14 households, Quadrant II the category of material poverty decreased from 5 households to 1 household ladder. And the results of this study indicate that the welfare and poverty indices of the CIBEST model increase. The value of the welfare index increased by 26%, the material poverty index decreased by 26%. It was concluded that the productive zakat of BAZNAS SU after being measured by the CIBEST approach was effective, namely being able to increase welfare and reduce poverty.Â